The Practice of Islamic Economics in North Sumatra: Kingdom History and the Modern Era - Muhammad Kharazi (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
Studies related to Islamic economic practices carried out by the kingdoms in North Sumatra until the modern era have not specifically investigated much. This study is focused on the practice of Islamic economics in North Sumatra in the royal era until the process of its development until today's modern era. This study used a historical approach with the library research method (library research method) to collect data using a literature review. The data collection technique was carried out by collecting documentation on the traces of the Islamic economy in North Sumatra. The results obtained from the research show that Islamic economic practices in North Sumatra have been carried out by Islamic kingdoms in North Sumatra in seven activity sectors, namely the real sector, social finance, public finance, monetary economy, international trade, legislation, and institutional activities. This is inseparable from the big role in the spread of Islam in North Sumatra. Furthermore, along with the times, economic practices based on Islamic principles as carried out by Islamic kingdoms in North Sumatra began to fade and were increasingly invisible until the birth of the modern Islamic economic era in North Sumatra as we know it today with Islamic banking as its main exposure.